Fixed combinations in the pragmatic management of hypertension: focus on aliskiren and hydrochlorothiazide as a single pill - Michel Burnier (Dove Medical Press, 2010)
Michel BurnierService of Nephrology and Hypertension, University Hospital, Lausanne, SwitzerlandAbstract: A majority of hypertensive patients need more than one antihypertensive drug to control their blood pressure. For this reason, most guidelines have introduced the possibility of prescribing fixed-dose combination therapies as first-line treatment in hypertension. Today, the concept of fixed-dose combinations has evolved and the term single pill combination might become more appropriate to reflect the large choice of drug combinations available on the market. Recently, a new single pill combination has been launched which combines the first direct renin inhibitor aliskiren and low doses of hydrochlorothiazide. This paper reviews the potential advantages of single pill combinations and presents the first results obtained with the aliskiren/HCTZ single pill combination in hypertension.Keywords: hypertension, drug adherence, combination therapies, diuretics, renin inhibition